Effect of the OPHN1 novel variant c.1025+1 G>A on RNA splicing: insights from a minigene assay - Fei Yang; Minghui Wang (BMC, 2024)
Abstract This research analyzes the clinical data, whole-exome sequencing results, and in vitro minigene functional experiments of a child with developmental delay and intellectual disability. The male patient, aged 4, began experiencing epileptic seizures at 3 months post-birth and has shown developmental delay. Rehabilitation training was administered between the ages of one and two. There were no other significant family medical histories. Through comprehensive family exome genetic testing, a hemizygous variant in the 11th exon of the OPHN1 gene was identified in the affected child: c.1025 + 1G > A. Family segregation analysis confirmed the presence of this variant in the patient's mother, which had not been previously reported. According to the ACMG guidelines, this variant was classified as a likely pathogenic variant. In response to this variant, an in vitro minigene functional experiment was designed and conducted, confirming that the mutation affects the normal splicing of the gene's mRNA, resulting in a 56 bp retention on the left side of Intron 11. It was confirmed that OPHN1: c.1025 + 1G > A is the pathogenic cause of X-linked intellectual disabilities in the child, with clinical phenotypes including developmental delay and seizures.